Body disposal: spatial and temporal characteristics in Korean homicide - Sea, Jonghan (International journal of offender therapy and comparative criminology, 2018)
This study explores the body disposal patterns in a sample of 54 Korean homicides that occurred between 2006 and 2012. Based on information collected by the police during their investigation, factors that could influence body disposal patterns were examined, such as homicide classification, intention, whether an accomplice was present, and offender mental disorder. Bivariate analyses showed that the majority of the victims who were disposed of were acquaintances of the offenders. Moreover, several offenders were more likely to dispose of the dead body “within hours” of killing the victim. Dead bodies were usually recovered in agricultural areas, forest/wooded areas, as well as residential areas. It was also noteworthy that, in 47 cases, the offender had knowledge of the geographic area where the body was dumped. In cases of “expressive” homicide, victims were more likely to be disposed of somewhere far away (e.g., over 40 km) from the crime scene, whereas “instrumental” homicide victims appeared to be disposed of somewhere closer (e.g., within 30 km) to the crime scene. Results are discussed in light of their practical implications for homicide investigations.